MATERIAL STATUS OF FAMILIES WITH FOUR OR MORE CHILDREN (DOBOJ CASE STUDY) - Janković, Aleksandar B.; Savić, Dalibor; Damjenić, Mirjana (Politeia, 2020)
The material status of families with four or more children in the municipality of Doboj is analyzed, starting from the general assumption that most of these families belong to economically and socially disadvantaged social groups. The paper aims to analyze some of the indicators of the financial status of families with four or more children, and to compare them with those related to the ‘average family’ in the Republic of Srpska. The analysis is based on the findings of a survey conducted in the municipality of Doboj from the end of July 2017 to the beginning of February 2018. The paper first analyzes the basic indicators of material status - income, property, consumption, and household equipment, and then the overall material status of multi-member families expressed through a composite index.